Revisión de artículos sobre floculación de microalgas (2016)
In this paper, time evolution of publications about flocculation is presented, since the beginnings related to waste water treatment until new advances in technologies, new substances, and process integration. Information is analyzed in two parts: country where the investigation took place, source and number of publications by year. And, in the second part, information is classified according to microalgae specie, flocculant type, process conditions and outstanding results.